2016
DOI: 10.4236/jbm.2016.45002
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Psychological Suzhi and Mental Health among Chinese College Students

Abstract: Object: To explore the relationship between psychological suzhi and mental health among Chinese college students, and to gain psychological suzhi factors that are predictors for mental health. Method: By using stratified sampling method, an investigation was conducted among 734 subjects. They were assessed with the College Student Psychological Suzhi Scale (CSPS, including 3 subscales, 28 factors) and General Health Questionnaire-20 item (GHQ-20, including 3 subscales). Results: 1) Psychological suzhi score fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 8 publications
3
20
0
Order By: Relevance
“…Having these positive peer interactions can, in turn, prevent and alleviate social anxiety. This finding corroborates those of studies examining the association between psychological suzhi and mental health, which have found that psychological suzhi positively relates to mental health [44]. Thus, the current finding adds empirical support for the relationship model of psychological suzhi and mental health [45].…”
Section: Discussionsupporting
confidence: 91%
“…Having these positive peer interactions can, in turn, prevent and alleviate social anxiety. This finding corroborates those of studies examining the association between psychological suzhi and mental health, which have found that psychological suzhi positively relates to mental health [44]. Thus, the current finding adds empirical support for the relationship model of psychological suzhi and mental health [45].…”
Section: Discussionsupporting
confidence: 91%
“…The total score of college students' IA was significantly negatively correlated with the total score of psychological suzhi; that is, the better the psychological suzhi, the lower the tendency for IA. Previous studies have shown that psychological suzhi and mental health problems are significantly negatively correlated (Wang et al, 2016). Therefore, this study indirectly validates previous studies showing that mental health problems are significantly positively correlated with IA tendencies Huang et al (2010).…”
Section: Relationship Between Psychological Suzhi and Internet Addictionsupporting
confidence: 90%
“…Previous studies have indicated that psychological suzhi plays an important role in individual psychology. Psychological suzhi is closely and positively related to mental health Internet addiction among college students (Wang et al, 2016). Zhang and Wang (2012) suggested that the relationship between psychological suzhi and mental health is similar to the relationship between "essence" and "performance".…”
Section: Psychological Suzhimentioning
confidence: 99%
“…From another perspective, young adolescents may have not yet developed sufficient competency in relying on PsyCap to deal with adversity without external support. Although regarded as a psychological resource that benefits mental health, PsyCap gradually builds up through adolescence (Wang et al, 2016 ). As they get older, adolescents may reduce their reliance on perceived social support and utilize their internal strength (Archer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%